PEMBERDAYAAN PEREMPUAN DALAM PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES) MELALUI PEMANFAATAN POTENSI SEKTOR PERTANIAN (STUDI KASUS DI DESA KADU ELA KECAMATAN CADASARI KABUPATEN PANDEGLANG) - Kurniawanto, Hadi; Anggraini, Yusniah (Jurnal Kebijakan Pembangunan Daerah, 2019)
Women's empowerment is one that needs to be a concern in the development of human resources, this is because up to now the quality of women is still lagging behind men, in terms of various indicators, one of which is the low female literacy rate, labor force participation rate (TPAK) women are low and MMR is still high. Women's participation in agricultural development and food security in Kadu Ela Village, Cadasari Subdistrict, Pandeglang Regency is very strategic, especially in the development of Rural-Owned Enterprises (BUMDes). Potential of food security that is owned by the people of Kadu Ela Village, Cadasari District is the main capital in developing existing local potentials. The purpose of the study was to determine the driving factors and obstacles as well as the role of women's empowerment in efforts to develop BUMDes through the utilization of local potential in Kadu Ela Village, Cadasari District, Pandeglang Regency. The results of the study show that the implementation of the Women's Empowerment program has been carried out at the stages of counseling and training, but has not been maximized in the activities of assistance, monitoring, evaluation, promotion and marketing strategies and partnerships. So that the women's empowerment program has not yet comprehensively and continuously maximized the potential for food security and the local wisdom of the community in developing post-harvest processing products.